KEHAMILAN TIDAK DIINGINKAN PADA REMAJA BELUM MENIKAH, IBU HAMIL BANYAK ANAK (KEBOBOLAN ALAT KONTRASEPSI) DAN PEMERKOSAAN DI PUSKESMAS TARUMAJAYA - Sirait, Lenny Irmawaty; Khaerunisa M, Ida; Wulansari, Puput; Riska, Riska; Lorensyah, Sintia Amilia; Fajahra, Tara Amelia; Salsabyla, Zahra Firly (Jurnal Ayurveda Medistra, 2026)
Unwanted pregnancy (KTD) is a pregnancy that for some reason, whose existence is not wanted by one or both of the baby's prospective parents. KTD is caused by a lack of complete and correct knowledge about the process of pregnancy and methods of preventing pregnancy due to acts of rape and failure of contraceptives. Unwanted pregnancies can be experienced by unmarried and married couples, teenagers, young couples, middle-aged women, even family planning acceptors, upper class, middle class and lower class. This study aims to find out some of the psychological needs for unwanted pregnancies in the Tarumajaya Health Center area. This type of research is a qualitative approach. This research was conducted at the Tarumajaya Health Center, North Bekasi City. The analysis technique used is descriptive data analysis technique, namely by collecting factual data and describing it. The results of the study found that for unwanted pregnancies in adolescents, the average age was 16-17 years before high school. Factors that cause unwanted pregnancies in adolescents are due to the lack of parental attention and free access to social media. For unwanted pregnancies in pregnant women, the average loss occurs in mothers who use KB injections for 3 months because the time for family planning visits is late. And for unwanted pregnancies in cases of rape not found or not at the Tarumajaya Health Center.